Effects of Adipose-derived Mesenchymal Stem Cell Exosomes on Corneal Stromal Fibroblast Viability and Extracellular Matrix Synthesis - Ting Shen; Qing-Qing Zheng; Jiang Shen; Qiu-Shi Li; Xing-Hui Song; Hong-Bo Luo; Chao-Yang Hong; Ke Yao (Chinese Medical Journal, 2018)
Background: Corneal stromal cells (CSCs) are components of the corneal endothelial microenvironment that can be induced to form a functional tissue-engineered corneal endothelium. Adipose-derived mesenchymal stem cells (ADSCs) have been reported as an important component of regenerative medicine and cell therapy for corneal stromal damage. We have demonstrated that the treatment with ADSCs leads to phenotypic changes in CSCs in vitro. However, the underlying mechanisms of such ADSC-induced changes in CSCs remain unclear. Methods: ADSCs and CSCs were isolated from New Zealand white rabbits and cultured in vitro. An Exosome Isolation Kit, Western blotting, and nanoparticle tracking analysis (NTA) were used to isolate and confirm the exosomes from ADSC culture medium. Meanwhile, the optimal exosome concentration and treatment time were selected. Cell Counting Kit-8 and annexin V-fluorescein isothiocyanate/propidium iodide assays were used to assess the effect of ADSC- derived exosomes on the proliferation and apoptosis of CSCs. To evaluate the effects of ADSC- derived exosomes on CSC invasion activity, Western blotting was used to detect the expression of matrix metalloproteinases (MMPs) and collagens. Results: ADSCs and CSCs were successfully isolated from New Zealand rabbits. The optimal concentration and treatment time of exosomes for the following study were 100 μg/ml and 96 h, respectively. NTA revealed that the ADSC-derived exosomes appeared as nanoparticles (40–200 nm), and Western blotting confirmed positive expression of CD9, CD81, flotillin-1, and HSP70 versus ADSC cytoplasmic proteins (all P < 0.01). ADSC-derived exosomes (50 μg/ml and 100 μg/ml) significantly promoted proliferation and inhibited apoptosis (mainly early apoptosis) of CSCs versus non-exosome-treated CSCs (all P < 0.05). Interestingly, MMPs were downregulated and extracellular matrix (ECM)-related proteins including collagens and fibronectin were upregulated in the exosome-treated CSCs versus non-exosome-treated CSCs (MMP1: t = 80.103, P < 0.01; MMP2: t = 114.778, P < 0.01; MMP3: t = 56.208, P < 0.01; and MMP9: t = 60.617, P < 0.01; collagen I: t = −82.742, P < 0.01; collagen II: t = −72.818, P < 0.01; collagen III: t = −104.452, P < 0.01; collagen IV: t = −133.426, P < 0.01, and collagen V: t = −294.019, P < 0.01; and fibronectin: t = −92.491, P < 0.01, respectively). Conclusion: The findings indicate that ADSCs might play an important role in CSC viability regulation and ECM remodeling, partially through the secretion of exosomes.